KOMUNIKASI VERBAL DAN NONVERBAL PADA KOMUNITAS GAME CLASH OF CLANS (Studi CMC pada Komunitas Indo ShadowsArmy): VERBAL AND NONVERBAL COMMUNICATION IN CLASH OF CLANS GAME COMMUNITY (CMC Study of Indo ShadowsArmy Community) - Aprilianti Pratiwi; Naila Hakamihya Maqamah (IPB University, 2018)
ABSTRACTAs a result of technological advances, many communities are now formed in the world of electronic communication. This study analyzes verbal and non verbal communication that occurs in the Clash of Clans game community, named Indo ShadowArmy. This study interviewed 6 members of Indo ShadowArmy. The methodology used in this study is qualitative with descriptive approach. Verbal and non-verbal communication in the Indo ShadowArmy community are: Indo ShadowArmy community members do not use words with abbreviated words and use of words, interpersonal conversations and unified narratives, calls on the regular Line application are light calls that are only used for member forces others, using a lot of terms in COC games, serious conversations that took place in the forum chatting took place during the war, the use of irony was never done, quite often using paralinguistic accounts that approach emoticons, calculating time for various topics that were very observing, have a fixed online schedule every day,